1998
DOI: 10.1002/(sici)1521-3757(19980116)110:1/2<160::aid-ange160>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Drei-Komponenten-Kupplung von Alkyliodiden, 1,3-Dienen und Carbonylverbindungen durch aufeinanderfolgende Bildung von radikalischen und anionischen Spezies mit CrCl2

Abstract: Als mildes Reduktionsmittel ist Chrom(II) in der Lage, zwischen Alkyliodiden, Alkylradikalen und Allylradikalen zu diskriminieren: Das Alkylradikal ist in Gegenwart von CrII so langlebig, daß es mit einem 1,3‐Dien reagieren kann, und das dabei entstehende Allylradikal bildet nach rascher Einelektronenreduktion eine Allylchrom(II)‐Spezies, die an einen Aldehyd unter Bildung des Drei‐Komponenten‐Produkts addiert [siehe z. B. Gl. (a)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Takai et al have shown that Fürstner's conditions also allow to render the three-component coupling of a secondary or tertiary alkyl iodide, a 1,3-diene, and an aldehyde catalytic in CrCl 2 . This unconventional reaction, relying on an interesting interplay of radical and anionic species, is discussed in more detail in section VI A.…”
Section: B Chromium-catalyzed Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Takai et al have shown that Fürstner's conditions also allow to render the three-component coupling of a secondary or tertiary alkyl iodide, a 1,3-diene, and an aldehyde catalytic in CrCl 2 . This unconventional reaction, relying on an interesting interplay of radical and anionic species, is discussed in more detail in section VI A.…”
Section: B Chromium-catalyzed Processesmentioning
confidence: 99%
“…In addition to the direct insertion of Cr(II) into allylic substrates, other methods for the preparation of allylchromium(III) species do exist. A rather unconventional approach is a three-component coupling reaction of a secondary or tertiary alkyl iodide, a 1,3-diene, and an aldehyde (Scheme ) . It is assumed that the Cr(II) first reacts with the alkyl halide to afford the secondary or tertiary radical, which upon addition to the diene delivers an allyl radical; the latter is rapidly reduced by excess Cr(II) to the corresponding allylchromium intermediate which finally adds in the regular regio- and stereoselective manner to the aldehyde component .…”
Section: Allylchromium(iii) Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Surprisingly, h 2 coordination of the triflate ligand in mononuclear late transition metal complexes was not reported until 1998, and the reactivity of these uncommon complexes has yet to be examined. [4,6] (4), P3-Rh1-O2 95.78 (7), P2-Rh1-O2 158.82 (7), P2-Rh1-O3 95.38 (7), P3-Rh1-O3 158.96 (7), O2-Rh1-O3 63.48 (9).…”
Section: Kazuhiko Takai* Ryotaro Morita and Chika Toratsumentioning
confidence: 97%
“…C2-Positionen, wobei 2-Alkylmethyl-3-buten-1-ole entstehen. [17] Von den Synthesemöglichkeiten und der Leichtigkeit fasziniert, mit der Dimethylzink, 1,3-Butadien und Benzaldehyd in dieser Reihenfolge in Abwesenheit von Phosphanliganden unter sehr milden Bedingungen Ni 0 -katalysiert miteinander reagieren, variierten wir die Carbonylverbindungen, um die Anwendungsbreite dieser Reaktion zu prüfen (Tabelle 1, Nr. 1 ± 5).…”
Section: Experimentellesunclassified